Los efectos jurídicos de la caducidad de la prisión preventiva, en los juzgados de garantías penales de la provincia de Pichincha, en el periodo de enero a diciembre del año 2011 - Samaniego Samaniego, Erika Mabel (2013)
Once completed the investigation process of the project titled: “The legal effects of the expiration of the preventive detention, in the courts of criminal guarantees of the Province of Pichincha, in the period from January to December of the year 2011”, it has been possible to determinate that the preventive detention must not be the general rule, as it is expressly established, that the reasonable limits prescribed bylaw; in the cases of crimes complex, this period are not enough to cover the who le process; I consider that it is necessary to review and reform our Law, according to the reality of our country. The thesis is divided into four chapters: the first is relates with the objectives, characteristics and legal nature of the detention, al soitre fers to the principles which must be observed and applied, among these we have: the principle of jurisdictionally, innocence, exceptionality, proportionality, provisionally, immediacy, legality and speed, it also exposes what is the due process